International Peace and Security - Rusan Novokmet, Rutvica (International Law From A Central European Perspective, 2022)
Maintenance of international peace and security has been the principal goal of the international community for centuries, but after the end of the Second World War States were determined more than ever to achieve that goal by creating firm legal, political, and institutional foundations for long-lasting peace. The international community committed itself to the international cooperation through organs and mechanisms of global and regional organizations. Particular significance was given to the formation of the international and regional legal framework of human rights protection, emphasizing that the respect of human rights is one of the main preconditions for fruitful international cooperation and a long-lasting peace. The United Nations serves as the global co-ordinator of the application of States’ obligations under international law through the collective security system and the network of subsidiary bodies. On the other hand, the role of regional international organizations in establishing an adequate legal framework for the preservation of peace and security, as well as for the respect of human rights and the rule of law, is of immeasurable importance. This chapter seeks to explore the efficiency of the international legal framework as well as institutional and diplomatic mechanisms provided by the United Nations and the leading regional organizations (NATO and the Organization for Security and Co-operation in Europe) that are responsible for the promotion, protection, and supervision of the Member States’ compliance with their international obligations, particularly from the point of view of Central European States. The author concludes that the most significant role of international organizations is in the continuous advancement of the responsibility of all actors involved to create a solid and long-lasting basis for the maintenance of international peace and security through the respect for human rights, democratic values, and the rule of law. KEYWORDS: international peace and security, international organizations, international cooperation, human rights protection, rule of law